Effects of short-term drought, nitrogen application and their interactions on the composition and functional genes of soil microbial communities in alfalfa grassland on the Loess Plateau - Wang, Ruobing; Zhang, Jingui; Ma, Tao; Lv, Wenqiang; Zhang, Zhixin; Shen, Yuying; Yang, Qian; Wang, Xianzhi; Li, Jiaxuan; Xiang, Qian; Lv, Long; Zhang, Jianjun; et al. (Frontiers in Sustainable Food Systems, 2023)
Drought and nitrogen addition are important factors influencing soil microorganisms and changes in the soil environment. In the future, droughts will become more frequent, shorter, and more severe. However, little is known about the soil organic carbon components, enzyme activity, and composition, structure, and functional genes of soil microbial communities under short-term drought and nitrogen application conditions. In this study, we used metagenomics sequencing technology to explore the changes in the composition and functional genes of soil microbial communities under short-term drought, nitrogen application, and their interactions in the artificial grasslands of the Loess Plateau. The results indicated that (I) short-term drought, nitrogen application, and their interactions all increased the particulate organic carbon (POC) content. (II) Short-term drought increased the contents of soil microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN), as well as soil enzyme activity. (III) Short-term drought significantly increased the bacterial alpha diversity, whereas the interactions of short-term drought and nitrogen application enhanced the fungal alpha diversity. (IV) The interactions of short-term drought and nitrogen application inhibited Fusarium to prevent plant diseases. (V) Short-term drought enriched the relative abundance of genes related to carbon cycling and amino acid metabolism, while nitrogen application reduced genes related to carbon cycling but enriched genes related to glycan biosynthesis and metabolism. These results clearly showed that, short-term drought altered the composition and functional genes of soil microbial communities. Our research suggests that in the event of frequent short-term droughts in the future, nitrogen addition can be considered to maintain the diversity of soil microbial communities and sustain soil carbon and nitrogen cycling.